2015
DOI: 10.1159/000363341
|View full text |Cite
|
Sign up to set email alerts
|

Event-Related Synchronization and Desynchronization of High-Frequency Electroencephalographic Activity during a Visual Go/No-Go Paradigm

Abstract: Objective: High-frequency electroencephalography (EEG) activity has been observed in association with cognitive processing, including stimulus perception, consciousness and selective attention, in humans. The aim of this study was to compare visual-motor integrated processing between execution and inhibition of a motor response using event-related synchronization (ERS) and desynchronization (ERD) in the 15- to 80-Hz range and to investigate a relationship between event-related potentials (ERPs) and ERS/ERD in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Power in the gamma band (33-60 Hz) reflects active engagement (i.e., in feature integration, attention, and movement preparation, depending on the cortical area) [119,120]. In controls, changes in gamma band power for activation and inhibition networks [93,[121][122][123][124]. The pattern of gamma band activity was similar to the peripheral attention network described by Corbetta and colleagues [125], and appeared to be relatively intact in PD.…”
Section: Frequency Specific Cortical Oscillatory Powersupporting
confidence: 52%
“…Power in the gamma band (33-60 Hz) reflects active engagement (i.e., in feature integration, attention, and movement preparation, depending on the cortical area) [119,120]. In controls, changes in gamma band power for activation and inhibition networks [93,[121][122][123][124]. The pattern of gamma band activity was similar to the peripheral attention network described by Corbetta and colleagues [125], and appeared to be relatively intact in PD.…”
Section: Frequency Specific Cortical Oscillatory Powersupporting
confidence: 52%
“…Our finding that tracing performance was still degraded by the sensory incongruence at the end of the experimental session argues in favor of continuous processes to solve the spatial problem and is therefore consistent with the observed beta and gamma ERDs in the right frontal cortex. The gamma ERD revealed in the left frontal region could have, in turn, contributed to inhibit motor actions that are normally appropriate in the context of non-biased visual feedback (Iijima et al, 2015).…”
Section: Changes Of Neural Oscillations In Other Cortical Regionsmentioning
confidence: 98%
“…Our results showed that gamma-mediated connectivity was increased when participants were exposed to a Go cue. In animals, the relationship between gamma power and movement preparation has received support from studies using intracellular recordings 37 , 38 , suggesting a specific role of high-frequency gamma activity during motor inhibition/execution (for a review see Wardak 2011). Alternatively, it could be hypothesized that the observed changes in gamma activity may reflect a re-balance of the theta/gamma coupling in response to the changes in theta activity, given that these frequencies naturally occur in the same brain regions and interact with each other 40 .…”
Section: Discussionmentioning
confidence: 99%